Progressive genetic modifications of porcine cardiac xenografts extend survival to 9 months. (31st March 2022) - Mohiuddin, Muhammad M.; Goerlich, Corbin E.; Singh, Avneesh K.; Zhang, Tianshu; Tatarov, Ivan; Lewis, Billeta; Sentz, Faith; Hershfeld, Alena; Braileanu, Gheorghe; Odonkor, Patrick; Strauss, Erik; Williams, Brittney; et al.
Abstract: We report orthotopic (life‐supporting) survival of genetically engineered porcine cardiac xenografts (with six gene modifications) for almost 9 months in baboon recipients. This work builds on our previously reported heterotopic cardiac xenograft (three gene modifications) survival up to 945 days with an anti‐CD40 monoclonal antibody‐based immunosuppression. In this current study, life‐supporting xenografts containing multiple human complement regulatory, thromboregulatory, and anti‐inflammatory proteins, in addition to growth hormone receptor knockout (KO) and carbohydrate antigen KOs, were transplanted in the baboons. Selective "multi‐gene" xenografts demonstrate survival greater than 8 months without the requirement of adjunctive medications and without evidence of abnormal xenograft thickness or rejection. These data demonstrate that selective "multi‐gene" modifications improve cardiac xenograft survival significantly and may be foundational for paving the way to bridge transplantation in humans.